PERSPEKTIF GENDER DALAM BUKU AJAR AL-ARABIYAH BAINA YADAIK - Nur Hadi (Lugawiyyat, 2020)
Analysis of gender perspectives in the textbook al-Arabiyah Baina Yadaik is very important to identify how much gender bias is contained in the textbook. This type of research is library research and includes descriptive qualitative research. This study uses Milles and Huberman's interactive analysis techniques. The gender bias found in the textbook al-Arabiyah Baina Yadaik volumes 1 and 2 by the Arabiyah li al-Jami' Team (Abd al-Rahman ibn Ibrahim al-Fauzan, et al) has an average of 62.5% (high category) reviewed from the display of images and 51.26% (medium category) in terms of sentence descriptions so that al-Arabiyah Baina Yadaik volumes 1 and 2 can be included as gender biased textbooks.